Mengurai Kerancuan Istilah Strategi dan Metode Pembelajaran - Fanani, Ahwan (Fakultas Ilmu Tarbiyah dan Keguruan, UIN Walisongo, Semarang, 2014)
This paper attempts to describe confused term of strategy and method learning. The key term in the field of education, especially in aspect learning, are ap-proach, model, strategy, method, and technology. The five words have a concep-tual distinction and two other terms cause confusion, i.e.: strategies and meth-ods. Diversity and confusion of these terms occur both in learning practice and in the study of the theory. This study shows that the existence of the phenomenon of the use of the strategies and methods term that are relatively loose and even they are used interchangeable. There is no agreement in the literature that exam-ined on applicative relationship between the two terms above. It was further confirmed that both terms have the same meaning field.Keyword: learning, strategy, method, confusion